Incorporar las TIC estratégicamente : un diseño mixto para entender la innovacion educativa en el sector público (2018)
The e-maturity is an institutional indicator to measure the level of progress in the integration of ICT in support of educational processes. Given that in Colombia this indicator has only been applied in higher education under particular assumptions in this sector, this paper aims to show the relevance of applying this indicator in the context of public education but articulated to other factors and instruments that allow to understand the complexity of Integrate ICT into an institution. In order to do this, a study of mixed nature manages to adapt, validate and pilot a set of instruments that aim not only to measure but to understand the relationship between e-maturity and the processes of educational innovation in a public institution in Bogota. As part of the findings is the absence of strategic planning to integrate ICT in institutions that even having high technological endowment present levels of development of ICT skills very basic in its teaching. It shows the importance of adapting and using the different devices and guidelines that the Ministry of Education produces but which often remain underutilized or unknown in the context of public education.--Tomado del Formato de Documento de Grado.